â€œI start learning English through speakingâ€: Social agency demand and inter-school readiness for Indonesian young English learners - Setyarini, Sri; Musthafa, Bachrudin; Muslim, Ahmad Bukhori (Indonesian Journal of Applied Linguistics, 2020)
Preserving Indonesian as a national identity and institutional readiness to perform the national curriculum 2013 instruction has become a critical factor in the exclusion of English as a compulsory subject at the elementary school level. This leaves rooms for teachers’ confusion and creativity, leading to various practices at different school clusters, depending on parental demands and school readiness. This study thus tries to cast light on the social agency demand and inter-school readiness for young learners in the Indonesian EFL pedagogical contexts. This instrumental case study portrays the practices of English language teaching at three clusters of Indonesian primary schools; local, national, and independent, as well as responses of parents and students to these practices. Involving 4-6 grade students and English teachers of six primary schools, the data were garnered through classroom observation, interviews, and document analysis. The findings revealed that although teaching English to young learners is somehow communicative and fun, it more emphasises literacy skills (reading, writing, and grammar), particularly at local schools as the majority cluster across the country. Since English is a non-phonetic language, this literacy-focused practice is rather contradictory to what parents as social agencies expect, that is, to develop their children’s English oral proficiency. The study also offers ways by which teachers and schools can accommodate this social agency’s needs for speaking skills by focusing more on student-centred and oral English proficiency activities and assessment.